Relationship of thoracic fat depots with coronary atherosclerosis and circulating inflammatory biomarkers - Maurovich-Horvat, Pál; Schlett, Christopher L. (Obesity, 2015)
Objective: The aim of the study was to determine the relationship of various thoracic fat depots with the presence and extent of coronary artery plaque and circulating biomarkers. Methods: In 342 patients (52 ± 11 years, 61% male, BMI 29.1 ± 5.9 kg/m2) with coronary computed tomography (CT), angiography, we measured the fat volume in four thoracic depots (pericoronary, epicardial, periaortic, extracardiac), assessed coronary plaque, and determined the circulating levels of C-reactive protein, tumor necrosis factor alpha, plasminogen activator inhibitor-1, monocyte chemoattractant protein-1, and adiponectin. The extent of coronary plaque was classified into three groups: 0, 1−3, and >3 segments. Results: Patients with plaque (n =169, 49%) had higher volumes of all four fat depots as compared to patients without plaque (all P < 0.01), despite similar BMI (P = 0.18). Extracardiac fat was most strongly correlated with BMI (r = 0.45, P < 0.001), while pericoronary fat was least (r = 0.21, P < 0.001). Only pericoronary fat remained associated with coronary plaque in adjusted analyses. Inflammatory biomarkers showed a positive correlation with pericoronary fat (all P < 0.0001), whereas adiponectin was not associated with this fat compartment (P = 0.60) and showed a negative correlation with all other fat depots (all P < 0.001). Conclusions: Pericoronary fat is independently associated with coronary artery disease (CAD). Its correlation with inflammatory biomarkers suggests that while systemic inflammation plays a role in the pathogenesis of CAD, there are additional local effects that may exist.